Heating canarian greenhouse with a passive solar water–sleeve system: Effect on microclimate and tomato crop yield. (August 2019) - Gourdo, L.; Fatnassi, H.; Bouharroud, R.; Ezzaeri, K.; Bazgaou, A.; Wifaya, A.; Demrati, H.; Bekkaoui, A.; Aharoune, A.; Poncet, C.; Bouirden, L.
Highlights: Study of a simple and economic system for heating an agricultural greenhouse. Study of the passive solar heating system effects on the development of T. Absoluta . This system reduces the cost of heating and does not pollute the environment. This system improves the greenhouse microclimate and tomato production. Abstract: Heating greenhouses is indispensable for plant development particularly in winter when air temperature is lower. In that sense, passive solar heating is a promising alternative compared to classic methods such as fossil fuels that are cost impacted and harmful to the environment. The current work is devoted to the study of the effect of a solar heating system using black plastic sleeves filled with water on the microclimate, tomato yield and the dynamic population of the tomato key pest, Tuta absoluta ( Lepidoptera: Gelechiidae ) in canarian greenhouses. The results show that the use of this heating system, improves the nighttime temperature inside the greenhouse by 3.1 °C and reduce by 10% the relative humidity compared to the control greenhouse. This microclimate improvement has a positive impact on the tomato production. It has increased by 35% compared to the control greenhouse. It was also noted that the presence of this heating system lead to a decrease in the development the population of T. absoluta in the heated greenhouse. Based on these results, the solar passive water–sleeve heating system can be an eco-friendly tool to prevent intensive use of fuel fossil and negative effect on the environment.